PENERAPAN ETIKA KRISTEN DALAM PEMELIHARAAN LINGKUNGAN HIDUP - Firman; Mustakim (Parakletos : Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Ethics becomes a benchmark and standard of values for regulating human moral life. Ethics also applies to environmental aspects. There are moral rules that apply to the environment. Christian ethics, in particular, presupposes moral action on God's revelation in the Bible. However, Christian ethics also needs to be applied to answer current environmental problems. The purpose of this study was written to explain the understanding of Christian ethics and environmental maintenance and explain the application of Christian ethics in environmental maintenance. The method used is a qualitative research method with a descriptive approach. The result of this study is that Christian ethics emphasizes that Christians care for the environment not because of the environmental crisis that occurs and not because of the rules made by humans, but to glorify God. There are at least three applications of Christian ethics in the maintenance of the environment, namely building an attitude of service, building an attitude of solidarity, and building an attitude of peace.